EKSPLORASI EFEK MODERASI DIMENSI BUDAYA TERHADAP PENERIMAAN TEKNOLOGI INTERNET MASYARAKAT YOGYAKARTA - Haris Sriwindono (PENERBIT LAFADZ JAYA, 2022)
The most popular model of technology acceptance related to information technology is the Unified Theory of Acceptance and Use of Technology model originating from developed countries. If applied in developing countries, it may not be appropriate, given the different cultures. In this study, a technology acceptance model will be developed by incorporating cultural factors or dimensions to make it suitable for Indonesia. The cultural dimensions used are the dimensions found by Hofstede, namely Power Distance, Individualism, Masculinity, Long Term Orientation and User Avoidance. In this study the Masculinity dimension was not used because this dimension is not so visible in Indonesia. This research was conducted using quantitative methods, factor analysis and path analysis using Structure Equation Modelling. The cultural dimension is placed as a moderating variable. The results of this study, it was found that the cultural dimension of Power Distance had a positive effect on the relationship between Effort Expectancy and Behavioral Intention and between Performance Expectancy and Behavioral Intention.. The cultural dimension of Individualsm has a positive effect on the relationship between Effort Expectancy and Behavioral only. The cultural dimension of User Avoidance has a positive effect on the relationship between Social Infuence and Behavioral Intention. Social influence has a direct effect on Behavioral Intention, indicating that environmental factors really greatly influence the intention to use the internet. Keywords: technology acceptance, cultural dimension, moderating variable